Assessing the impact of a home-based stroke rehabilitation programme: a cost-effectiveness study. Issue 17 (14th August 2019) - Allen, Laura; John-Baptiste, Ava; Meyer, Matthew; Richardson, Marina; Speechley, Mark; Ure, David; Markle-Reid, Maureen; Teasell, Robert
Abstract: Background: Stroke is often a severe and debilitating event that requires ongoing rehabilitation. The Community Stroke Rehabilitation Teams (CSRTs) offer home-based stroke rehabilitation to individuals for whom further therapy is unavailable or inaccessible. The objective of this study was to evaluate the cost-effectiveness of the CSRT programme compared with a "Usual Care" cohort. Methods: We collected data on CSRT clients from January 2012 to February 2013. Comparator data were derived from a study of stroke survivors with limited access to specialised stroke rehabilitation. Literature-derived values were used to inform a long-term projection. Using Markov modelling, we projected the model for 35 years in six-month cycles. One-way, two-way, and probabilistic sensitivity analyses were performed. Results were discounted at 3% per year. Results: Results demonstrated that the CSRT programme has a net monetary benefit (NMB) of $43, 655 over Usual Care, and is both less costly and more effective (incremental cost = −$17, 255; incremental effect = 1.65 Quality Adjusted Life Years [QALYs]). Results of the probabilistic sensitivity analysis revealed that incremental cost-effectiveness of the CSRT programme is superior in 100% of iterations when compared to Usual Care. Conclusions: The study shows that CSRT model of care is cost-effective, and should be considered when evaluating potential stroke rehabilitation delivery methods. Implications for Rehabilitation: Ongoing rehabilitation following stroke is imperative for optimal recovery. Home-based specialised stroke rehabilitation may be an option for individuals for whom ongoing rehabilitation is unavailable or inaccessible. The results of this study demonstrated that home-based rehabilitation is a cost-effective means of providing ongoing rehabilitation to individuals who have experienced a stroke.